Electrode composition for lithium secondary battery, electrode slurry, electrode, and lithium secondary battery
By using a specific type and proportion of monomer copolymer in the adhesive of a lithium secondary battery, the problem of volume expansion of the negative electrode active material of silicon-based compound during charging and discharging is solved, and the high strength and excellent adhesion of the battery are achieved Compatibility and flexibility thus improve the phase stability and service life of the battery.
Patent Information
- Application Number
- CN202380048374.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-06
- Filing Date
- 2023-12-07
- Publication Date
- 2025-02-07
AI Technical Summary
When the silicon-based compound in a lithium secondary battery is used as the negative electrode active material, the volume expansion problem caused by repeated charging and discharge will lead to blocking of the conductive path and deteriorating the battery characteristics.
A copolymer of (meth)acrylamide monomer, (meth)acrylic acid monomer, (meth)acrylonitrile monomer and metal-substituted (meth)acrylic acid monomer in the binder and satisfy the specific The weight ratio relationship is to adjust the glass transition temperature and pH of the adhesive to ensure high strength, excellent adhesion and flexibility of the electrode.
It effectively prevents volume expansion caused by repeated charging and discharge, and improves the phase stability and service life of the battery.
Smart Images

Figure BDA0005197778890000131 
Figure BDA0005197778890000151
Abstract
Description
Technical Field
[0001] This application claims the priority and benefit of Korean Patent Application Nos. 10-2022-0184423 and 10-2023-0175688, filed with the Korean Intellectual Property Office on December 26, 2022 and December 6, 2023, respectively, the entire contents of which are incorporated herein by reference.
[0002] This specification relates to an electrode composition for a lithium secondary battery, an electrode paste, an electrode, and a lithium secondary battery. Background Art
[0003] Due to the rapid growth in the use of fossil fuels, the demand for alternative or clean energy is increasing, and as part of this trend, the most actively studied area is the field of power generation and power storage using electrochemical reactions.
[0004] Currently, representative examples of electrochemical devices using such electrochemical energy include secondary batteries, and their fields of use are increasing.
[0005] Meanwhile, with the technological development and increasing demand for mobile devices, the demand for secondary batteries has increased rapidly. Accordingly, lithium secondary batteries having characteristics such as high energy density and voltage, long cycle life, and low self-discharge rate have been commercialized and widely used. In addition, as an electrode for a high-capacity lithium secondary battery, active research has been conducted on preparing a high-density electrode having a higher energy density per unit volume.
[0006] Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. In particular, the negative electrode includes a negative electrode active material, and a silicon-based particle having a high charge and discharge capacity can be used as the negative electrode active material.
[0007] In particular, recently, in response to the demand for secondary batteries with high-energy electrodes, active research has been conducted on a method of increasing the capacity by using a silicon-based compound (such as Si / C or SiOx (0 < x < 2)), which has a capacity 10 times that of a graphite-based material, as a negative electrode active material. However, compared with existing graphite-based materials, the problem with silicon-based compounds is that, due to the generation of hydrogen during repeated charge and discharge processes, volume expansion occurs to block the conduction path, resulting in deterioration of battery characteristics.
[0008] To solve the volume expansion caused by the above-mentioned repeated charge and discharge processes, research has also been conducted on the composition of the binder, and as a result, binder polymers with strong stress have been studied. In particular, attempts have been made to change the composition and content of the binder polymer.
[0009] In addition, in order to ensure conductivity of the negative electrode, the secondary battery further includes a conductive material. Although carbon black and the like are mainly used in the related art, in order to increase the capacity of the secondary battery, single-walled carbon nanotubes (SWCNTs) having a thin and elongated shape have been used.
[0010] In order to solve these problems, various methods have been discussed, and one of these methods is a method capable of easily adjusting the physical properties of an adhesive by changing the type and / or content of constituent components constituting the adhesive so that the adhesive has a strong stress. Summary of the invention
[0011] [Technical issues]
[0012] The present inventors have found that by including a (meth)acrylamide monomer as a main constituent element of a binder in a predetermined content range, the glass transition temperature (Tg) value of the binder can be easily adjusted, and therefore, in the future, electrode slurry, electrode and lithium secondary battery containing the binder can solve the above-mentioned problems by ensuring high strength, excellent adhesion and flexibility, and high electrode density.
[0013] In addition, the inventors have attempted to make improvements in various aspects, such as improving the capacity by including a silicon-based active material as an electrode active material, using single-walled carbon nanotubes as a conductive material to further improve the capacity of the secondary battery, using a water-based adhesive with high dispersibility as a binder to improve the compatibility of the single-walled carbon nanotubes, or preventing electrode expansion that occurs with repeated charging and discharging processes by adjusting the pH of the adhesive within a predetermined range, thereby completing the present invention.
[0014] Therefore, the present application is committed to providing an electrode composition for a lithium secondary battery, an electrode slurry, an electrode and a lithium secondary battery including the above-mentioned technical features.
[0015] [Technical solution]
[0016] An exemplary embodiment of the present specification provides an electrode composition for a lithium secondary battery, comprising: an electrode active material; a conductive material; and a binder, wherein the binder is a copolymer of a (meth)acrylamide monomer, a (meth)acrylic acid monomer, a (meth)acrylonitrile monomer, and a metal-substituted (meth)acrylic acid monomer, and satisfies the following relational formulas (I) to (III).
[0017] 1≤[AM] / ([AA-H]+[AA-M])≤10 Relationship (I)
[0018] 0.01≤[AA-H]([AA-H]+[AA-M])≤0.5 Relationship (II)
[0019] 2≤([AM]+[AA-H]+[AA-M]) / [AN]≤10000 Relationship (III)
[0020] In equations (I) to (III),
[0021] Based on 100 parts by weight of the adhesive,
[0022] [AM] represents the weight parts of (meth)acrylamide monomer,
[0023] [AA-H] represents the weight parts of (meth)acrylic acid monomers,
[0024] [AA-M] represents the weight parts of the metal (M)-substituted (meth)acrylic acid monomer,
[0025] [AN] represents the weight parts of (meth)acrylonitrile monomer.
[0026] In addition, an exemplary embodiment of the present specification provides an electrode slurry for a lithium secondary battery, which includes the electrode composition for a lithium secondary battery and a solvent.
[0027] In addition, the exemplary embodiment of the present specification provides a negative electrode for a lithium secondary battery, which includes an electrode active material layer on one surface or both surfaces of an electrode current collector layer, the electrode active material layer including the electrode slurry for a lithium secondary battery.
[0028] Finally, an exemplary embodiment of the present specification provides a lithium secondary battery including: a first electrode; a second electrode; a separator disposed between the first electrode and the second electrode; and an electrolyte, wherein either the first electrode and the second electrode is the above-described electrode for the lithium secondary battery.
[0029] [Beneficial Effects]
[0030] The electrode composition for a lithium secondary battery of the present application includes an electrode active material having a large charge and discharge capacity, but provides the following effects: preventing the volume expansion problem caused by repeated charge and discharge, having excellent phase stability, and further improving the service life of the battery. DETAILED DESCRIPTION
[0031] Before describing the present invention, some terms are first defined.
[0032] When a component “comprises” a constituent element in the present specification, unless specifically described otherwise, this does not mean that other constituent elements are excluded but means that other constituent elements may be further included.
[0033] In this specification, "p to q" means a range of "p or more and q or less".
[0034] In the present specification, the fact that a polymer includes a monomer as a monomer unit means that the monomer participates in a polymerization reaction and is therefore included in the polymer as a repeating unit. In the present specification, when a polymer includes a monomer, it is interpreted as the same as when the polymer includes a monomer as a monomer unit.
[0035] In this specification, "polymer" should be understood to be used in a broad sense, including copolymers, unless otherwise specified as a "homopolymer".
[0036] In this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are polystyrene conversion molecular weights measured by measuring molecular weight using commercially available monodisperse polystyrene polymers (standard samples) with various polymerization degrees as standard materials by gel permeation chromatography (GPC). In this specification, unless otherwise specified, molecular weight refers to weight average molecular weight.
[0037] Hereinafter, the present invention will be described in detail so that those skilled in the art to which the present invention belongs can easily implement the present invention. However, the present invention can be implemented in various different forms and is not limited to the following description.
[0038] <Lithium Secondary Battery Electrode Composition>
[0039] An exemplary embodiment of the present specification provides an electrode composition for a lithium secondary battery, comprising: an electrode active material; a conductive material; and a binder, wherein the binder is a copolymer of a (meth)acrylamide monomer, a (meth)acrylic acid monomer, a (meth)acrylonitrile monomer, and a metal-substituted (meth)acrylic acid monomer, and satisfies the following relational formulas (I) to (III).
[0040] 1≤[AM] / ([AA-H]+[AA-M])≤10 Relationship (I)
[0041] 0.01≤[AA-H]([AA-H]+[AA-M])≤0.5 Relationship (II)
[0042] 2≤([AM]+[AA-H]+[AA-M]) / [AN]≤10000 Relationship (III)
[0043] In equations (I) to (III),
[0044] Based on 100 parts by weight of the adhesive,
[0045] [AM] represents the weight parts of (meth)acrylamide monomer,
[0046] [AA-H] represents the weight parts of (meth)acrylic acid monomers,
[0047] [AA-M] represents the weight parts of the metal (M)-substituted (meth)acrylic acid monomer,
[0048] [AN] represents the weight parts of (meth)acrylonitrile monomer.
[0049] According to the exemplary embodiment, when the binder satisfies the relational expressions (I) to (III), shrinkage and expansion caused by charge / discharge of the battery may be suppressed, and life-time use performance may be improved.
[0050] According to an exemplary embodiment of the present invention, the metal (M) may be Li, Na, Ca, or a combination thereof.
[0051] In the exemplary embodiment of the present specification, the (meth)acrylamide monomer may be included in an amount of 40 parts by weight or more and 80 parts by weight or less based on 100 parts by weight of the binder.
[0052] In the electrode composition for a lithium secondary battery according to the exemplary embodiment, since the content of the (meth)acrylamide is included in the above range, shrinkage and expansion caused by charge / discharge of the battery may be further suppressed, and lifespan performance may be further improved.
[0053] In the exemplary embodiment of the present specification, the glass transition temperature (Tg) of the binder may be 125° C. or more and 150° C. or less.
[0054] In the electrode composition for a lithium secondary battery according to the exemplary embodiment, since Tg is controlled within the above range, shrinkage and expansion caused by charge / discharge of the battery may be further suppressed, and lifespan performance may be further improved.
[0055] In the present specification, the term "(meth)acrylic acid" may include methacrylic acid or acrylic acid.
[0056] In the present specification, the content of (meth)acrylamide may be about 40 parts by weight or more, about 45 parts by weight or more, or about 50 parts by weight or more, or about 80 parts by weight or less, about 75 parts by weight or less, or about 70 parts by weight or less, based on 100 parts by weight of the adhesive.
[0057] In the present specification, a polymerization initiator is used to prepare the copolymer, and ammonium persulfate may be used as an example of the polymerization initiator, but the polymerization initiator is not limited thereto.
[0058] In the present specification, the fact that the adhesive includes multiple compounds having a specific ratio (expressed in parts by weight or weight ratio) may mean that each compound (e.g., (meth)acrylamide, (meth)acrylic acid, (meth)acrylonitrile and metal-substituted (meth)acrylic acid) is contained as a monomer of the adhesive polymer.
[0059] In an exemplary embodiment of the present specification, based on 100 parts by weight of the electrode composition for a lithium secondary battery, the amount of the electrode active material present may be 60 parts by weight or more.
[0060] In an exemplary embodiment of the present specification, based on 100 parts by weight of the electrode composition for a lithium secondary battery, the content of the electrode active material may be about 60 parts by weight or more, preferably about 65 parts by weight or more, more preferably about 70 parts by weight or more, or about 95 parts by weight or less, preferably about 90 parts by weight or less.
[0061] In an exemplary embodiment of the present specification, the electrode active material may include one or more selected from the group consisting of a silicon-based active material and a carbon-based active material.
[0062] In the present specification, the capacity of the silicon-based active material is 10 times that of the carbon-based active material. Therefore, when the silicon-based active material is applied to an electrode, particularly a negative electrode, an electrode with a higher level of energy density can be achieved, and even a thinner thickness than when only the carbon-based active material is included.
[0063] In another exemplary embodiment of the present specification, when the electrode active material is composed of a silicon-based active material and a carbon-based active material, the composition ratio between the silicon-based active material and the carbon-based active material may be from 2:98 to 30:70.
[0064] The electrode active material of the exemplary embodiment includes a carbon-based active material as a main component, and thus the following effects can be further provided: the volume expansion of the electrode caused by charging and discharging is slight, and the conductivity of the electrode is excellent.
[0065] In an exemplary embodiment of the present specification, the silicon-based active material may include one or more of SiOx (x = 0), SiOx (0 < x < 2), SiC, and Si alloys.
[0066] In the present specification, the electrode active material includes silicon particles, which may exist, for example, in a crystalline or amorphous form. Specifically, the silicon particles may preferably be spherical particles, but are not limited thereto.
[0067] In an exemplary embodiment of the present specification, the electrode composition for a lithium secondary battery is a negative electrode composition. Therefore, the silicon-based active material, the conductive material, and the binder can all be used for the negative electrode composition.
[0068] The negative electrode composition is characterized in that by using a specific conductive material and a specific binder, even when a silicon-based active material having a significantly high capacity is used within the above range, the volume expansion rate during charging / discharging can be suppressed, and even when including the above range, the performance of the negative electrode does not deteriorate, and the output characteristics during charging and discharging are excellent.
[0069] In this specification, SiOx where x is 2 is not included. 2 The situation is that the SiO 2 It does not react with lithium ions and therefore cannot store lithium. Therefore, it is preferred that x falls within the range of the exemplary embodiment.
[0070] In this specification, the silicon-based active material may be Si / C composed of a composite of Si and C, or Si.
[0071] In the present specification, two or more silicon-based active materials may be mixed and used.
[0072] In the present specification, in some cases, a carbon-based active material may be included in addition to the above-mentioned silicon-based active material.
[0073] Generally, it is known that the capacity of silicon-based active materials is 10 times that of carbon-based active materials, and therefore, when silicon-based active materials are applied to electrodes, especially negative electrodes, it is expected that electrodes with a high level of energy density can be achieved even with a smaller thickness.
[0074] In the exemplary embodiment of the present specification, the content of SiOx (x=0) may be 70 parts by weight or more based on 100 parts by weight of the silicon-based active material.
[0075] In another exemplary embodiment of the present specification, the silicon-based active material may include SiOx (x=0) in an amount of 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, or 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less, based on 100 parts by weight of the silicon-based active material.
[0076] In another exemplary embodiment, the average particle size (D50) of the silicon-based active material may be 3 μm to 10 μm.
[0077] In this specification, "Dn" refers to the particle size distribution, and refers to the particle size at the n% point in the cumulative distribution of the number of particles according to the particle size. That is, D50 is the particle size at the 50% point in the cumulative distribution of the number of particles according to the particle size (average particle size), D90 is the particle size at the 90% point in the cumulative distribution of the number of particles according to the particle size, and D10 is the particle size at the 10% point in the cumulative distribution of the number of particles according to the particle size. At the same time, the particle size distribution can be measured using a laser diffraction method. Specifically, after dispersing the powder to be measured in a dispersion medium, the particle size distribution is calculated by introducing the resulting dispersion into a commercially available laser diffraction particle size measuring device (such as Microtrac S3500) to measure the difference in the diffraction pattern according to the particle size when the particles pass through the laser beam.
[0078] In the exemplary embodiment of the present specification, the carbon-based active material may include one or more selected from the group consisting of artificial graphite, natural graphite, hard carbon, and soft carbon.
[0079] In the related art, only graphite-based compounds are generally used as negative electrode active materials, but recently, as the demand for high-capacity batteries increases, attempts to use silicon-based active materials or to use silicon-based active materials by mixing with carbon-based active materials have increased in order to increase capacity.
[0080] In the exemplary embodiment of the present specification, the content of the conductive material may be 0.3 parts by weight or more and 40 parts by weight or less, based on 100 parts by weight of the electrode composition for a lithium secondary battery.
[0081] In another exemplary embodiment, the conductive material may be contained in an amount of 10 parts by weight or more and 40 parts by weight or less, preferably 10 parts by weight or more and 30 parts by weight or less, and more preferably 10 parts by weight or more and 25 parts by weight or less, based on 100 parts by weight of the electrode composition.
[0082] In yet another exemplary embodiment, the conductive material may include one or more selected from the group consisting of a dot-shaped conductive material, a plane-shaped conductive material, and a line-shaped conductive material.
[0083] In this other exemplary embodiment, the conductive material may be a mixture of a dot-shaped conductive material and a line-shaped conductive material.
[0084] In this specification, the point-shaped conductive material can be used to enhance the conductivity of the negative electrode, and refers to a point-shaped or spherical conductive material having conductivity without causing chemical changes. Specifically, the point-shaped conductive material can be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenylene derivatives, and can preferably include carbon black in terms of achieving high conductivity and excellent dispersibility.
[0085] In this specification, the planar conductive material can increase the surface contact between the silicon particles in the negative electrode to improve the conductivity and simultaneously suppress the disconnection of the conductive path due to volume expansion. The planar conductive material can be expressed as a plate-like conductive material or a block-like conductive material. Examples of planar conductive materials can include at least one selected from the group consisting of plate-like graphite, graphene, graphene oxide, and graphite sheets, and can preferably be plate-like graphite.
[0086] In the present specification, the linear conductive material may be a carbon nanotube. The carbon nanotube may be a bundle-type carbon nanotube. The bundle-type carbon nanotube may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle-type" used herein refers to a secondary shape in the form of a bundle or a rope, in which a plurality of carbon nanotube units are arranged side by side or entangled, and in this arrangement, the longitudinal axes of the carbon nanotube units are substantially the same. In the carbon nanotube unit, the graphene sheet has a cylindrical shape with a nanometer-sized diameter and has a sp 2 In this case, the carbon nanotube unit can exhibit the characteristics of a conductor or a semiconductor, depending on the structure and angle of the curling of the graphene sheet. Compared with the tangled carbon nanotubes, the bundled carbon nanotubes can be evenly dispersed during the preparation of the negative electrode, and can improve the conductivity of the negative electrode by smoothly forming a conductive network in the negative electrode.
[0087] In another exemplary embodiment, the conductive material may be a negative electrode conductive material.
[0088] In this specification, the negative electrode conductive material is applied to the negative electrode and has a completely different configuration from the positive electrode conductive material applied to the positive electrode. In other words, the negative electrode conductive material is used to capture the contact points between the silicon-based active material (the volume expansion of the electrode is very large due to charging and discharging), while the positive electrode conductive material is used to impart partial conductivity and play a buffering role during rolling, so the negative electrode conductive material and the positive electrode conductive material have different structures and functions.
[0089] In an exemplary embodiment of the present invention, the content of the binder may be 3 parts by weight or more and 30 parts by weight or less based on 100 parts by weight of the electrode composition for a lithium secondary battery.
[0090] In another exemplary embodiment of the present specification, the content of the binder may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, or may be 3 parts by weight or more, preferably 5 parts by weight or more, based on 100 parts by weight of the electrode composition for a lithium secondary battery.
[0091] In another exemplary embodiment, the binder may be a negative electrode binder.
[0092] According to exemplary embodiments, when a silicon-based compound is used for a negative electrode, it has excellent bonding strength with a conductive material and a binder, compared to an existing carbon-based negative electrode.
[0093] In an exemplary embodiment of the present invention, the adhesive may be a water-based adhesive.
[0094] In an exemplary embodiment of the present invention, the binder may be a copolymer further including one or more selected from the group consisting of a (meth)acrylic acid monomer, a (meth)acrylonitrile monomer, and a metal-substituted (meth)acrylic acid monomer.
[0095] According to an exemplary embodiment of the present invention, the pH of the binder may be 4.5 or more and 7.5 or less. For example, the pH of the binder may be 4.5 or more, 4.6 or more, or 4.7 or more, or 7.5 or less, 7.4 or less, or 7.3 or less.
[0096] In this specification, the hydrogen ion concentration (pH) is measured using a Seven Compact pH meter manufactured by Mettler-Toledo Co., Ltd.
[0097] In another exemplary embodiment, the weight average molecular weight of the binder is 100,000 g / mol or more and 1,500,000 g / mol or less.
[0098] <Electrode slurry for lithium secondary batteries>
[0099] In an exemplary embodiment of the present invention, an electrode slurry including the above-mentioned electrode composition for a lithium secondary battery and a solvent is provided.
[0100] In another exemplary embodiment of the present invention, the solvent includes those known in the art. For example, the solvent may be distilled water or NMP.
[0101] The electrode slurry of the present invention is a negative electrode slurry, and therefore the electrode composition may involve the negative electrode slurry.
[0102] In some cases, when the viscosity of the electrode slurry is controlled within a suitable range by appropriately adjusting the average particle size (D50) of the silicon-based active material and adjusting the specific surface area of the particles, the dispersion of the components in the slurry (e.g., conductive material, binder, silicon-based active material, etc.) can be improved. Therefore, the contact area between the components is improved, so that the conductive network can be maintained, the capacity retention rate can be improved, and the current density non-uniformity phenomenon during charge / discharge can also be prevented.
[0103] In addition, in some cases, the viscosity of the electrode slurry can be adjusted to 5000 cps to 6000 cps. Therefore, when one surface or both surfaces of the electrode current collector layer are coated with the electrode slurry in the future, the coating property and the storability are excellent.
[0104] <Electrode for lithium secondary battery>
[0105] Another exemplary embodiment of the present invention provides an electrode for a lithium secondary battery, the electrode including: an electrode current collector layer; and an electrode active material layer, wherein the electrode slurry is applied on one surface or both surfaces of the electrode current collector layer.
[0106] In another exemplary embodiment of the present invention, the electrode is a negative electrode, and thus, the electrode current collector layer, the electrode slurry, and the electrode active material layer all relate to the negative electrode.
[0107] In this specification, the negative electrode current collector layer generally has a thickness of 1 μm to 100 μm. The negative electrode current collector layer is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel surface-treated with carbon, nickel, titanium or silver, and aluminum-cadmium alloys can be used. In addition, the negative electrode current collector layer may also form microscopic irregularities on its surface to increase the adhesion strength of the negative electrode active material. The negative electrode current collector layer can be used in various shapes, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0108] In an exemplary embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the thickness of the negative electrode current collector layer is 1 μm or more and 100 μm or less, and the thickness of the negative electrode active material layer is 20 μm or more and 500 μm or less.
[0109] However, the thickness may be variously changed according to the type and purpose of the negative electrode used, and is not limited thereto.
[0110] <Lithium Secondary Battery>
[0111] An exemplary embodiment of the present invention provides a lithium secondary battery including: a first electrode; a second electrode; a separator disposed between the first electrode and the second electrode; and an electrolyte, wherein either the first electrode or the second electrode is the above-described electrode for a lithium secondary battery.
[0112] Specifically, the lithium secondary battery according to the exemplary embodiment may include the above-described electrode for a lithium secondary battery.
[0113] Specifically, the first electrode may be a cathode and the second electrode may be a cathode, or the first electrode may be a cathode and the second electrode may be a cathode.
[0114] The secondary battery of the exemplary embodiment of the present specification may specifically include the above-mentioned negative electrode for lithium secondary battery. Specifically, the lithium secondary battery may include a negative electrode, a positive electrode, a separator and an electrolyte disposed between the positive electrode and the negative electrode, and the negative electrode is the same as the above-mentioned negative electrode. Since the negative electrode has been described in detail, its specific description will be omitted.
[0115] The positive electrode may include a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector and including a positive electrode active material.
[0116] In the positive electrode, the positive electrode collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel materials surface-treated with carbon, nickel, titanium or silver, etc., can be used. Moreover, the positive electrode collector can generally have a thickness of 3 μm to 500 μm, and microscopic irregularities can be formed on the surface of the collector to improve the adhesion of the positive electrode active material. The positive electrode collector can be used in various shapes, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0117] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may include: a layered compound, such as lithium cobalt oxide (LiCoO 2 ) or lithium nickel oxide (LiNiO 2 ) or a compound substituted with one or more transition metals; lithium iron oxide, such as LiFe 3 O 4 ; Lithium manganese oxide, such as Li 1+c1 Mn 2-c1 O 4 (where c1 is 0 to 0.33), LiMnO 3 、LiMn 2 O 3 and LiMnO 2 ; Lithium copper oxide (Li 2 CuO 2 ); Vanadium oxides, such as LiV 3 O 8 、V 2 O 5 and Cu 2 V 2 O 7 ; LiNi 1-c2 M c2 O 2 (wherein M is at least one selected from Co, Mn, Al, Cu, Fe, Mg, B or Ga, c2 = 0.01 to 0.3) represented by Ni-type lithium nickel oxide; represented by the formula LiMn 2-c3 M c3 O 2 (wherein M is at least one selected from Co, Ni, Fe, Cr, Zn or Ta, c3 = 0.01 to 0.1) or Li 2 Mn 3 MO 8(wherein M is at least one selected from Fe, Co, Ni, Cu or Zn) represented by a lithium manganese composite oxide; wherein a portion of the Li atoms in the formula are replaced by alkaline earth metal ions LiMn 2 O 4 ; etc., but not limited thereto. The positive electrode may be lithium metal.
[0118] The positive electrode active material layer may include a positive electrode conductive material and a positive electrode binder in addition to the above-mentioned positive electrode active material.
[0119] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation as long as it has electronic conductivity and does not cause chemical changes in the constituted battery. Specific examples thereof include: graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one of them or a mixture of two or more thereof can be used.
[0120] Alternatively, the positive electrode binder is used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode current collector. Its specific examples may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof may be used.
[0121] The separator separates the negative electrode from the positive electrode and provides a mobile path for lithium ions, and can be used without particular restriction, as long as it is generally used as a separator in a secondary battery, and in particular, a separator having excellent moisture retention ability to the electrolyte and low resistance to the movement of electrolyte ions can be used. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin polymer (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer), or a laminated structure of more than two layers thereof. Moreover, a common porous nonwoven fabric can be used, for example, a nonwoven fabric formed by high melting point glass fiber or polyethylene terephthalate fiber, etc. In addition, a coated separator including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a single layer or multilayer structure can be selectively used.
[0122] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, or molten inorganic electrolytes, which can be used to prepare lithium secondary batteries, but are not limited thereto.
[0123] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.
[0124] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone (NMP), propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl pyrophosphate and ethyl propionate can be used.
[0125] In particular, among carbonate organic solvents, cyclic carbonates ethylene carbonate and propylene carbonate can be preferably used because these cyclic carbonates are high-viscosity organic solvents with high dielectric constants and thus dissociate lithium salts well, and such cyclic carbonates can be more preferably used because these cyclic carbonates can be mixed in an appropriate proportion with low-viscosity and low-dielectric-constant chain carbonates (e.g., dimethyl carbonate and diethyl carbonate) and used to prepare an electrolyte with high conductivity.
[0126] As the metal salt, a lithium salt can be used. The lithium salt is a substance that is easily dissolved in a non-aqueous electrolyte. For example, as the anion of the lithium salt, a metal salt selected from F - , Cl - ,I - 、NO 3 - 、N(CN) 2 - , BF 4 - , ClO 4 - PF 6 - ,(CF 3 ) 2 PF 4 - ,(CF 3 ) 3 PF 3 - ,(CF 3 ) 4 PF2 - , (CF 3 ) 5 PF - , (CF 3 ) 6 P - , CF 3 SO 3 - , CF 3 CF 2 SO 3 - , (CF 3 SO 2 ) 2 N - , (FSO 2 ) 2 N - , CF 3 CF 2 (CF 3 ) 2 CO - , (CF 3 SO 2 ) 2 CH - , (SF 5 ) 3 C - , (CF 3 SO 2 ) 3 C - , CF 3 (CF 2 ) 7 SO 3 - , CF 3 CO 2 - , CH 3 CO 2 - , SCN - , and (CF 3 CF 2 SO 2 ) 2 N - One or more of the following.
[0127] In the electrolyte, in order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity and increase the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, at least one additive may be further included, for example, a halogenated alkylene carbonate compound (such as difluoroethylene carbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glycol dimethyl ether, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride.
[0128] An exemplary embodiment of the present invention provides a battery module including the secondary battery as a unit cell and a battery pack including the battery module. The battery module and the battery pack include a secondary battery having high capacity, high rate characteristics and cycle characteristics, and can therefore be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.
[0129] <Method for Manufacturing Lithium Secondary Battery>
[0130] In another exemplary embodiment of the present invention, a method for manufacturing a lithium secondary battery is provided, the method comprising: mixing an electrode composition for a lithium secondary battery with a solvent to prepare an electrode slurry for a lithium secondary battery; applying the electrode slurry for a lithium secondary battery on one surface or both surfaces of an electrode collector layer; and drying the electrode collector layer to which the electrode slurry for a lithium secondary battery is applied, the electrode composition for a lithium secondary battery, the solvent, the electrode collector layer and the coating method being as described above.
[0131] In the present specification, as drying, a method known in the art such as air drying is used.
[0132] In the present specification, steps such as rolling performed after the above steps are known in the art.
[0133] Hereinafter, preferred embodiments will be presented to facilitate understanding of the present invention, but these embodiments are provided only to illustrate the present invention, and it is obvious to those skilled in the art that various changes and modifications can be made within the scope and technical spirit of the present invention, and these changes and modifications naturally also fall within the scope of the appended claims.
[0134] Preparation Example. Preparation of Adhesive
[0135] <Preparation Examples 1 to 3 and Comparative Preparation Examples 1 to 3>
[0136] In a reactor equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube, each monomer (i.e., (meth)acrylamide (AM, using a 50% aqueous solution), (meth)acrylic acid (AA-H, using an 80% aqueous solution), (meth)acrylonitrile (AN) and metal (M)-substituted (meth)acrylic acid (AA-M)) was mixed in the following contents (based on weight ratio) described in the following Table 1, ammonium persulfate was added thereto as a polymerization initiator, and the resulting mixture was reacted at 75° C. for 8 hours, thereby preparing a polymer aqueous solution.
[0137] Thereafter, a 0.1 M sodium hydroxide aqueous solution was dropped into the polymer aqueous solution to prepare an aqueous adhesive having a desired pH (see Table 2).
[0138] [Table 1]
[0139]
[0140] The condition is
[0141] Relationship (I): [AM] / ([AA-H]+[AA-M])
[0142] Relationship (II): [AA-H]([AA-H]+[AA-M])
[0143] Relationship (III): ([AM]+[AA-H]+[AA-M]) / [AN]
[0144] In relational formulas (I) to (III), based on 100 parts by weight of the adhesive, [AM] represents parts by weight of (meth)acrylamide monomer, [AA-H] represents parts by weight of (meth)acrylic acid monomer, [AA-M] represents parts by weight of metal (M)-substituted (meth)acrylic acid monomer, and [AN] represents parts by weight of (meth)acrylonitrile monomer.
[0145] Example. Preparation of electrode slurry
[0146] Example 1
[0147] Si with d50 = 5.2 μm was used as the negative electrode active material, and three types of conductive materials: carbon black (SuperC65, produced by TIMCAL Ltd.), artificial graphite (SFG6L, produced by TIMCALLtd) and SWCNT were used as conductive materials. The water-based binder of Preparation Example 1 was mixed with other components so that the negative electrode active material: carbon black: artificial graphite: SWCNT: water-based binder = 80:3:6.3:0.7:12 (weight ratio), thereby preparing an electrode composition.
[0148] Thereafter, water was added as a solvent, and the content of water was adjusted in consideration of coatability, viscosity, and solid content so that the viscosity of the obtained electrode slurry was 5000 cps to 6000 cps.
[0149] Examples 2 and 3
[0150] Electrode slurries were prepared in the same manner as in Example 1, except that the water-based binders of Preparation Examples 2 and 3 were used, respectively.
[0151] Example 4
[0152] An electrode slurry was prepared in the same manner as in Example 1, except that 9:1 artificial graphite (QCG-N2, manufactured by Shanshan):SiO (E82, manufactured by DAEJOO ELECTRONIC MATERIALS Co., Ltd.) was used as the negative electrode active material.
[0153] Example 5
[0154] An electrode slurry was prepared in the same manner as in Example 1, except that 9:1 artificial graphite:SiC (SD5100A, manufactured by Sila Nanotechnologies Inc.) was used as a negative electrode active material.
[0155] Comparative Examples 1 to 3
[0156] Electrode slurries were prepared in the same manner as in Example 1, except that the water-based binders of Comparative Preparation Examples 1 to 3 were used, respectively.
[0157] Comparative Example 4
[0158] An electrode slurry was prepared in the same manner as in Comparative Example 1, except that artificial graphite:SiO at a ratio of 9:1 was used as the negative electrode active material.
[0159] Comparative Example 5
[0160] An electrode slurry was prepared in the same manner as in Comparative Example 1, except that 9:1 artificial graphite:SiC was used as the negative electrode active material.
[0161] Experimental example
[0162] Experimental Example 1. Measurement of the glass transition temperature (Tg) of the adhesive
[0163] The glass transition temperature (Tg) of each of the adhesives obtained in Preparation Examples 1 to 3 and Comparative Preparation Examples 1 to 3 was measured using DSC measurement increasing the temperature from -50 to 180° C. at intervals of 5° C. The results are shown in Table 2 below.
[0164] Experimental Example 2. Measurement of pH of Adhesive
[0165] The pH of each of the adhesives obtained in Preparation Examples 1 to 3 and Comparative Preparation Examples 1 to 3 was measured using a Seven Compact pH meter manufactured by Mettler-Toledo Co., Ltd. The results are shown in Table 2 below.
[0166] [Table 2]
[0167] Classification Tg(℃) pH Preparation Example 1 133 6.8 Preparation Example 2 138 6.4 Preparation Example 3 146 6.5 Comparative Preparation Example 1 114 4.6 Comparative Preparation Example 2 118 4.2 Comparative Preparation Example 3 152 6.4
[0168] According to Table 2 above, based on 100 parts by weight of the adhesive, in Preparation Examples 1 to 3 in which the content of the (meth)acrylamide monomer was 40 parts by weight or more and 80 parts by weight or less, the glass transition temperature of the adhesive was in the range of 125° C. or more and 150° C. or less. However, in Comparative Preparation Examples 1 to 3 in which the content of the (meth)acrylamide monomer was less than 40 parts by weight or more than 80 parts by weight, the glass transition temperature was less than 120° C. or more than 150° C.
[0169] Experimental Example 3. Battery Manufacturing and Battery Characteristics Evaluation
[0170] A copper foil having a thickness of 15 μm was coated with each electrode slurry of Examples 1 to 5 and Comparative Examples 1 to 5, and dried to form an electrode active material layer having a thickness of 48 μm on one surface of the copper foil, and the copper foil was punched into a circle having a diameter of 14 Φ (mm) to manufacture a test electrode (negative electrode). A metal lithium foil having a thickness of 0.3 mm was used as a positive electrode. A porous polyethylene sheet having a thickness of 0.1 mm was used as a separator. In addition, the following obtained product was used as an electrolyte: LiPF as a lithium salt was used as a 6 It was dissolved in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 at a concentration of about 1 mol / L.
[0171] The negative electrode, positive electrode, separator and electrolyte were sealed in a stainless steel container to manufacture a coin cell with a thickness of 2 mm and a diameter of 32 mm for evaluation. The coin cell was charged at a constant current of 0.05C until the voltage reached 0.01V, and discharged at a constant current of 0.05C until the voltage reached 1.5V to determine the discharge capacity and initial efficiency, and then, in the same voltage range as above, the cycle characteristics were carried out at a constant current of 0.2C, thereby conducting a capacity retention test, and the results are shown in Table 3 below.
[0172] [Table 3]
[0173]
[0174] As shown in Table 3 above, in the electrode slurries of Examples 1 to 5, based on 100 parts by weight of the binder, a binder having a (meth)acrylamide monomer content of 40 parts by weight or more and 80 parts by weight or less (the glass transition temperature is each 125° C. or more and 150° C. or less) is used, and the capacity retention rate of the battery manufactured therefrom is 79% or more. In contrast, in the electrode slurries of Comparative Examples 1 to 5, a binder having a (meth)acrylamide monomer content of less than 40 parts by weight or more than 80 parts by weight is used based on 100 parts by weight of the binder (the glass transition temperature of each binder does not satisfy the range of 125° C. or more and 150° C. or less), and the capacity retention rate of the battery manufactured therefrom is less than 70%.
Claims
1. An electrode composition for a lithium secondary battery, comprising: an electrode active material; Conductive materials; and a binder, wherein the binder comprises a copolymer of a (meth)acrylamide monomer, a (meth)acrylic acid monomer, a (meth)acrylonitrile monomer, and a metal-substituted (meth)acrylic acid monomer, and satisfies the following relational expressions (I) to (III): 1 ≤ [AM] / ([AA-H] + [AA-M]) ≤ 10 Relational expression (I) 0.01 ≤ [AA-H] / ([AA-H] + [AA-M]) ≤ 0.5 Relational expression (II) 2 ≤ ([AM] + [AA-H] + [AA-M]) / [AN] ≤ 10000 Relational expression (III) In relational expressions (I) to (III), based on 100 parts by weight of the copolymer, [AM] represents the parts by weight of the (meth)acrylamide monomer, [AA-H] represents the parts by weight of the (meth)acrylic acid monomer, [AA-M] represents the parts by weight of the metal (M)-substituted (meth)acrylic acid monomer, [AN] represents the parts by weight of the (meth)acrylonitrile monomer.
2. The electrode composition according to claim 1, wherein Based on 100 parts by weight of the copolymer, the content of the (meth)acrylamide monomer is 40 parts by weight or more and 80 parts by weight or less.
3. The electrode composition according to claim 1, wherein The glass transition temperature (Tg) of the copolymer is 125 °C or more and 150 °C or less.
4. The electrode composition according to claim 1, wherein Based on 100 parts by weight of the electrode composition for a lithium secondary battery, the amount of the electrode active material present is 60 parts by weight or more.
5. The electrode composition according to claim 1, wherein The electrode active material includes one or more selected from the group consisting of a silicon-based active material and a carbon-based active material.
6. The electrode composition according to claim 5, wherein The silicon-based active material includes one or more selected from the group consisting of SiOx with x = 0, SiOx with 0 < x < 2, SiC, and Si alloys.
7. The electrode composition according to claim 5, wherein The carbon-based active material includes one or more selected from the group consisting of artificial graphite, natural graphite, hard carbon, and soft carbon.
8. The electrode composition according to claim 1, wherein The conductive material includes one or more selected from the group consisting of a dot-shaped conductive material, a planar conductive material, and a linear conductive material.
9. The electrode composition according to claim 1, wherein The binder is an aqueous binder.
10. The electrode composition according to claim 1, wherein The pH of the binder is 4.5 or more and 7.5 or less.
11. An electrode paste for a lithium secondary battery, comprising the electrode composition according to any one of claims 1 to 10 and a solvent.
12. A lithium secondary battery electrode, comprising: an electrode current collector layer; and an electrode active material layer, wherein the electrode paste according to claim 11 is coated on one surface or both surfaces of the electrode current collector layer.
13. A lithium secondary battery comprising: A first electrode; A second electrode; A separator disposed between the first electrode and the second electrode; And an electrolyte, wherein either the first electrode or the second electrode is the lithium secondary battery electrode according to claim 12.